Development of Chemistry Teaching Materials with Demonstration Videos on the Acid–Base Concept to Support the Merdeka Curriculum - Nabilah, Hafizah; Hardeli, Hardeli (Journal of Educational Sciences, 2025)
The transition to the Merdeka Curriculum has significantly impacted Indonesia's education system, requiring both teachers and students to adopt more innovative and creative learning approaches. However, appropriate teaching materials are still limited, particularly for abstract topics such as acid–base concepts. This study aimed to develop chemistry teaching materials equipped with demonstration videos to support learning in accordance with the Merdeka Curriculum. The research employed an Educational Design Research (EDR) approach using Plomp’s development model, which includes preliminary research, prototyping, and assessment stages. Data were collected through interviews and questionnaires on validity and practicality, and analyzed using Aiken's V formula. The results showed a validity score of 0.85, indicating a high level of validity. Practicality tests showed a score of 94% from teachers and 92% from students, categorized as very high. These findings conclude that the developed acid–base teaching materials for Phase F senior high school students are valid and practical for implementation in Merdeka Curriculum learning.